Rapid charge transfer in TiO2/COF S-scheme heterojunction for boosting H2O2 photosynthesis and Rhodamine B degradation - Yanyan Zhao; Yong Zhang; Haiyan Tan; Chenbin Ai; Jianjun Zhang (Journal of Materiomics)
Cooperative coupling of hydrogen peroxide (H2O2) photosynthesis with organic pollutant degradation is promising strategy applied in chemical synthesis and environmental protection. Nonetheless, the photocatalytic performance is limited by sluggish photogenerated carrier separation and limited redox potentials. Herein, an S-scheme heterojunction was constructed by assembling the TiO2 nanoparticles and a Schiff-base COF together. The formed S-scheme TiO2/COF heterojunction can efficiently produce H2O2 and degrade Rhodamine B (RhB) synchronously. The S-scheme charge transfer mechanism in TiO2/COF composite is well unveiled by in situ irradiated X-ray photoelectron spectroscopy and DFT calculation. The femtosecond transient absorption spectra reveal the superior charge migration at interface between TiO2 and COF. The designed TiO2/COF composite shows drastically enhanced H2O2 yield of 1326 μmol·g−1·h−1 in RhB solution, and the AQY value of 4.11% under 420 nm monochromatic light irradiation is achieved. Meanwhile, 100% of RhB degraded under light irradiation for 40 min with TiO2/TD COF as photocatalyst. This work exemplifies a promising approach to design COF-based S-scheme heterojunction with ameliorative photocatalytic performance for simultaneous organic pollutants degradation and H2O2 production.